PENGARUH MATERI USWATUN HASANAH BERBANTUAN VIDEO TERHADAP HASIL BELAJAR PESERTA DIDIK DI MTsN PADANG PARIAMAN - Tri Widya Ananda; Sasmi Nelwati; Rilci Kurnia Illahi (UIN Imam Bonjol Padang, 2022)
Learning activities are basically a communication process. In the communication process, the educator acts as a communicator in charge of conveying learning messages to the recipients of the message, namely students. Educators must be able to package uswatun hasanah learning materials well so that the expected learning objectives can be achieved. Current field conditions indicate that learning materials are delivered using conventional methods where students are less active in the Akidah Akhlak learning process. Therefore, it takes a learning video media that can attract and foster students' learning enthusiasm, not only educators who are active in the learning process but students can also take an active and enthusiastic role in learning. This type of research is a quantitative experiment with a Pre-Test design. Post-Test Control Group Design. The population in this study were all students of class VIII MTsN 2 Padang Pariaman. To get the sample, it was done by selecting the Rondom Sampling sample. The results showed that the average value of the test scores for the Akhlak learning outcomes in the experimental class was 84 and the average scores for the Akidah Akhlak learning outcomes in the control class was 80,125. After testing the hypothesis using SPSS Version 22, it was obtained that a significant on both sides (2-tailed) was = 0.000, it was concluded that (0.000 < 0.05) at the 95% confidence interval. So the decision H0 is rejected and Ha is accepted, meaning that there are differences in learning outcomes using video-assisted Uswatun Hasanah material with learning using conventional methods on Akidah Akhlak subjects at MTsN 2 Padang Pariaman.